Close relationship between immunoglobulin secreting‐cells and Epstein–Barr virus reservoir in patients infected with HIV. Issue 1 (23rd September 2013) - Ouedraogo, David Eric; Tuaillon, Edouard; Rubbo, Pierre‐Alain; Bollore, Karine; Foulongne, Vincent; Reynes, Jacques; Vendrell, Jean‐Pierre
Abstract Individuals infected with HIV have higher circulating Epstein–Barr virus (EBV) DNA load compared to healthy carriers. This study investigated whether level of spontaneous immunoglobulin secreting cells, one of the major hallmarks of HIV infection, is associated with an increase of EBV DNA load in PBMCs and the spontaneous EBV lytic cycle ex vivo in patients infected with HIV. Spontaneous virus production by cells infected with EBV and EBV DNA loads in PBMCs from which CD8+ T‐cells were removed were measured in 20 HIV‐aviremic and 14 HIV‐viremic patients. The number of circulating immunoglobulin‐secreting cells (Ig‐SCs) and CD8+ T‐lymphocyte activation were also investigated. Patients with detectable HIV RNA in plasma exhibited higher spontaneous ex vivo EBV secretion and higher levels of EBV DNA in PBMCs than their aviremic counterparts. In the two groups observed, a positive correlation was found between PBMCs EBV DNA viral load and Ig‐SCs, CD38bright expression on CD8+ T‐cells and EBV DNA load in cell culture supernatants. These findings suggest that B‐cell polyclonal activation and B‐cell terminal differentiation into Ig‐SCs may fuel EBV DNA reservoir and promote EBV production ex vivo in patients infected with HIV. J. Med. Virol. 86:30–37, 2014. © 2013 Wiley Periodicals, Inc.